2016
DOI: 10.13189/aeb.2016.040403
|View full text |Cite
|
Sign up to set email alerts
|

Random Walk, Ergodicity versus Predictability – The Case of the Budapest Stock Exchange

Abstract: In financial markets, the term 'random walk' is frequently used in relation to price movement over a period of time. This highly expressive term simply means that prices do not follow a predictable trend, and so previous movements are unsuitable as a basis for speculation regarding future price changes. There exists, however, another model which is based on the ergodic theorem, and this says that past and present probability distribution define the probability distribution which will dictate future market pric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Kiragu and Mung'atu (2016) found generalized Pareto better fitted for daily returns from the Nairobi securities exchange. Iván and Zsolt (2016) found BUX daily return followed non-normality with flat-tailed. Corlu et al (2016) found generalized lambada better fitted than the normal distribution for daily returns from nineteen stock markets around the world.…”
Section: Introductionmentioning
confidence: 92%
“…Kiragu and Mung'atu (2016) found generalized Pareto better fitted for daily returns from the Nairobi securities exchange. Iván and Zsolt (2016) found BUX daily return followed non-normality with flat-tailed. Corlu et al (2016) found generalized lambada better fitted than the normal distribution for daily returns from nineteen stock markets around the world.…”
Section: Introductionmentioning
confidence: 92%
“…If technical analysis functions as a trading strategy for entry and exit, Machine Learning (ML) LSTM model can act as affirmative support for stock options. However, [27] research concludes that short-term predictability and forecast are impossible; the more time elapses between the appearance of choice and its consequences, the more certain it is for individuals to assume that their decisions must be made under ambiguous conditions circumstances.…”
Section: Introductionmentioning
confidence: 99%